Цифровая трансформация банковской системы в условиях становления и развития цифровой экономики - Степаненко, О.П. (Управляющие системы и машины, 2017)
Рассмотрена цифровая трансформация банковской системы в условиях становления и развития цифровой экономики, в том числе формирование цифровых активов системы, развития ее цифровой информационно-коммуникационной инфраструктуры и создания цифровых финансовых сетей промышленного Интернета. Розглянуто цифрову трансформацію банківської системи в умовах становлення та розвитку цифрової економіки, в тому числі формування цифрових активів системи, розвитку її цифрової інформаційно-комунікаційної інфраструктури та створення цифрових фінансових мереж промислового Інтернету. Purpose of the articlr is to analyze the processes of changes in the banking system in the conditions of formation and development of the digital economy, define the main problem issues and describe the concept of research and analysis of the processes of digital transformation of the banking system. The processes of digital transformation of the banking system in the conditions of the formation and development of the digital economy were investigated. The following and the primary objectives of the digital transformation of the banking system were identified: – formation of digital assets of the banking system; – development of the digital information and communication infrastructure of the banking system and the development of digital financial and banking services in the framework of financial support for the cross-border space of the digital economy; – the creation of digital financial networks of Internet of Things. The concept of research and analysis of the processes of digital transformation of the banking system in the context of the formation and development of the digital economy is described.